2009
DOI: 10.1021/nl903274q
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Antibacterial Coatings That Support Mammalian Cell Growth

Abstract: Bacterial infections present an enormous problem causing human suffering and cost burdens to healthcare systems worldwide. Here we present novel tunable antibacterial coatings which completely inhibit bacterial colonization by Staphylococcus epidermidis but allow normal adhesion and spreading of osteoblastic cells. The coatings are based on amine plasma polymer films loaded with silver nanoparticles. The method of preparation allows flexible control over the amount of loaded silver nanoparticles and the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
126
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 42 publications
3
126
0
Order By: Relevance
“…The study of plasma polymer coatings that could potentially be used in biomedical devices is an area of increasing research interest [1][2][3][4][5]. One of the most common classes of thin film treatments employed in biomaterial devices is that of 'low-fouling' or 'stealth' coatings [6].…”
Section: Introductionmentioning
confidence: 99%
“…The study of plasma polymer coatings that could potentially be used in biomedical devices is an area of increasing research interest [1][2][3][4][5]. One of the most common classes of thin film treatments employed in biomaterial devices is that of 'low-fouling' or 'stealth' coatings [6].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma polymers are easy to prepare by a well established technology of plasma polymerization. It has a long history of exploitation in a variety of applications, because it is non-toxic, transparent, with a very low surface tension, very good adhesion to any substrate, flexible, and it neither dissolves nor swells in a cell culture medium, insoluble in cold and hot solvents [4,5,6]. From the other hand nanodiamonds are of interest due to the combination of unique properties inherent to diamond and the specific surface structure of particles facilitating its functionalization [1].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous siloxan-based materials, including polymerized hexamethyldisiloxane (PPHMDS) are developed. PPHMDS was easy to prepare by a well established technology of plasma polymerization (Vasilev et al, 2010. PPHMDS has a long history of exploitation in a variety of applications, because it is non-toxic, transparent, with a very low surface tension, flexible, and it neither dissolves nor swells in a cell culture medium (Min-Hsien, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Si-DND samples, obtained by silinaztion are produced in order to prevent formation of DNDs aggregates (Baidakova, Vul', 2007). The incorporation of silver ions in the polymer, lead to production of samples that are highly efficient against bacterial colonization and allows the adhesion and spreading of mammalian cells (Vasilev K et al, 2010, Agarwal et al, 2009. It is found that the adhesion and proliferation of different types of cells on biomaterials depend on many surface characteristics, such as surface charge, wettability (hydrophobicity/hydrophilicity), chemistry, microstructure, roughness, and mechanical properties (Min-Hsien, 2009).…”
Section: Introductionmentioning
confidence: 99%